"To the rescue!" cartoon from 'The Case for the Insurance Bill' by Rt. Hon. David Lloyd George (1911)
1911 1880-1914 ""To the rescue!" cartoon from 'The Case for the Insurance Bill' by Rt. Hon. David Lloyd George" [T0186.jpg], 1911 The pamphlet is a reprint from 'Reynold's Newspaper' of a speech made by Lloyd George at Whitefield's Tabernacle, 14 October 1911.